2016
DOI: 10.18203/2320-1770.ijrcog20162090
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for urinary incontinence in pregnant women during late third trimester

Abstract: Conservative statistics estimate that 10% of women more than 18 years and 33% of women more than 40 years are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 18 publications
2
16
0
7
Order By: Relevance
“…The findings of this study showed that the prevalence of UI was relatively lower than the findings of studies done in India, Turkey, Brazil, and Malaysia which were 75.25%, 63.8%, 71%, 40%, 42.4%, and 84.5%, respectively. 5,6,9,[23][24][25] This observed difference in India and Turkey could be due to inclusion of third trimester only which has positive correlation with the occurrence of UI. 6,9 The additional possible explanation is that due to the increment of sample size utilized in the study done in Brazil and Turkey.…”
Section: Discussionmentioning
confidence: 95%
“…The findings of this study showed that the prevalence of UI was relatively lower than the findings of studies done in India, Turkey, Brazil, and Malaysia which were 75.25%, 63.8%, 71%, 40%, 42.4%, and 84.5%, respectively. 5,6,9,[23][24][25] This observed difference in India and Turkey could be due to inclusion of third trimester only which has positive correlation with the occurrence of UI. 6,9 The additional possible explanation is that due to the increment of sample size utilized in the study done in Brazil and Turkey.…”
Section: Discussionmentioning
confidence: 95%
“…Literatürde araştırma bulgusunu destekleyen çalışmalar mevcuttur. 14,16,27,29,34,38 BKİ'deki artış sonucunda, mesane üzerindeki artan karın içi basınca ve aşırı üretral mobiliteye bağlı olarak Üİ görülebilmektedir. 39 Çalışmada gebelikten önceki BKİ 25 ve üzerinde olan gebelerin ve gebeliğinde 18 kg ve üzerinde kilo alan gebelerin BKAÜYSÖ puan ortalaması BKİ normal sınırlarda olan gebelerin puan ortalamasından daha yüksektir (p<0,001).…”
Section: Verilerin Analiziunclassified
“…Literatürde araştırma bulgusunu destekleyecek şekilde sigara kullanmanın üriner inkontinans görülme sıklığını arttırdığını saptayan çalışmalar mevcuttur. 14,29,31 Kafein detrüsör kasını etkileyerek diüretik etki göstermektedir. 39 Araştırmada gebelikte kafein içeren içecek tüketimi ile alt üriner yol semptomları arasında önemli ilişki olduğu saptanmıştır (p<0,05).…”
Section: Verilerin Analiziunclassified
See 1 more Smart Citation
“…The prevalence of Urinary Incontinence (UI) greatly varies, mainly according to the type of population and the different age groups. During pregnancy, the prevalence of UI can reach 75.25% (1) . In the puerperium rates of 37.9% are noted, even after 12 years of childbirth (2) .…”
Section: Introductionmentioning
confidence: 99%